A simple new scoring system for predicting the mortality of severe acute pancreatitis: A retrospective clinical study. Issue 23 (5th June 2020) - Wang, Lei; Zeng, Yan-Bo; Chen, Jia-Yun; Luo, Qian; Wang, Rowan; Zhang, Ruijie; Zheng, Daniel; Dong, Yuan-Hang; Zou, Wen-Bin; Xie, Xiaoqing; Du, Yi-Qi; Li, Zhao-Shen
Abstract : Abstract: It is critical to accurately identify patients with severe acute pancreatitis (SAP) in a timely manner. This study aimed to develop a new simplified AP scoring system based on data from Chinese population. We retrospectively analyzed a consecutive series of 585 patients diagnosed with SAP at the Changhai hospital between 2009 and 2017. The new Chinese simple scoring system (CSSS) was derived using logistic regression analysis and was validated in comparison to 4 existing systems using receiver operating characteristic curves. Six variables were selected for incorporation into CSSS, including serum creatinine, blood glucose, lactate dehydrogenase, heart rate, C-reactive protein, and extent of pancreatic necrosis. The new CSSS yields a maximum total score of 9 points. The cut-offs for predicting mortality and severity (discriminating moderately SAP from SAP) were set as 6 points and 4 points respectively. Compared with 4 existing scoring systems, the area under the receiver operating characteristic of CSSS for prediction of mortality was 0.838, similar to acute physiology and chronic health evaluation II (0.844) and higher than Ranson's score (0.702, P  < .001), bedside index of severity in acute pancreatitis (0.615), and modified computed tomography severity index (MCTSI) (0.736). For predicting SAP severity, CSSS was the most accurate (0.834), followed by acute physiology and chronic health evaluation II (0.800), Ranson's score (0.702), MCTSI (0.660), and bedside index of severity in acute pancreatitis (0.570). Further, the accuracy of predicting pancreatic infection with CSSS was the highest (0.634), similar to that of MCTSI (0.641). A new prognostic scoring system for SAP was derived and validated in a Chinese sample. This scoring system is a simple and accurate method for prediction of mortality. Abstract : Supplemental Digital Content is available in the text